Impact of 18F-FDG PET/CT in Staging Patients With Small Cell Lung Cancer: A Systematic Review and Meta-Analysis - Martucci, Francesco; Pascale, Mariarosa; Valli, Maria Carla; Pesce, Gianfranco A.; Froesch, Patrizia; Giovanella, Luca; Richetti, Antonella; Treglia, Giorgio (Frontiers in Medicine, 2020)
Background Molecular imaging methods are currently used in the management of patients with lung cancer. Compared to non-small cell lung cancer (NSCLC), less data are available about the impact of molecular imaging by using fluorine-18-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) in staging patients with small cell lung cancer (SCLC). Performing a systematic review and meta-analysis we aimed to provide quantitative data about the impact of 18F-FDG PET/CT in staging SCLC. Methods A comprehensive literature search of studies on the use of 18F-FDG PET/CT in patients with SCLC was performed. Three different databases were screened (PubMed/MEDLINE, EMBASE and Cochrane library databases) until June 2019. Only articles describing the impact of 18F-FDG PET/CT in staging patients with SCLC were selected. A pooled analysis evaluating the change of binary SCLC staging (limited-stage versus extensive-stage disease) by using 18F-FDG PET/CT was carried out. Results Nine articles including 721 patients with SCLC were included in the systematic review. Compared to conventional staging, a superior diagnostic accuracy of 18F-FDG PET/CT was found. A change of binary SCLC staging by using 18F-FDG PET/CT was demonstrated in 15% (95% confidence interval: 9-21%) of patients with SCLC. Currently, it is not clearly demonstrated that the use of 18F-FDG PET/CT for staging may improve the survival outcome of patients with SCLC. Conclusions 18F-FDG PET/CT is a useful molecular imaging method for staging patients with SCLC because it can change the management in a significant number of patients. More large prospective studies and cost-effectiveness analyses on the impact of 18F-FDG PET/CT in staging patients with SCLC are needed.